State of wonder - Patchett, Ann. (New York : Harper, 2011)
Dr. Marina Singh, a research scientist with a Minnesota-based pharmaceutical company, is sent to Brazil after the death of her friend and colleague, to take up his mission of finding Dr.Annick Swenson, a ruthless woman, now in her seventies, who has been conducting research among the Lakashi tribe on a reputed miracle drug, and refuses to let anything stand in her way.
Library Journal Starred, April 2011
Pub Weekly, April 2011
Kirkus Starred, February 2011
Booklist, February 2011
Adult
Adult
Keywords: Scientists -- Fiction; Medicine -- Research -- Fiction; Jungles -- Amazon River Region -- Fiction; Scientists -- Fiction; Medicine -- Research -- Fiction; Jungles -- Amazon River Region -- Fiction